“Who do I look like?”: Kinning and resemblance in the experience of French donor conceived adults - Anaïs Martin (Antropologia, 2019)
This article questions the notion of kinning through the analysis of resemblance and transmission talk in the narratives of French donor offspring. Between February 2015 and May 2016, semi-structured interviews were conducted with 15 French sperm donor conceived adults. For most of them their conception had been a secret for part of their life. After the disclosure of the facts of their conception, donor offspring reassessed their kin relationships, integrating the new information into their narrative. The father’s absence of participation in procreation was integrated without denying his role and status as a father. The donor’s participation in procreation was also included in the narratives but he was not considered as kin. I thus argue that resemblance and transmission talk does not necessarily imply kinship and kinning. When it does refer to kin, it participates in a process of reaffirmation of family relations affected by disclosure, that I propose to describe as re-kinning.